Influence of melanin and macrophage activation on hearing loss in SLC26A4 deficient mice. - Natsuki Aoki; Ayako Maruyama; Toru Miwa; Natsuko Kurata; Keiji Honda; Yoshiyuki Kawashima; Takeshi Tsutsumi; Taku Ito (Neurobiology of Disease)
Hearing loss associated with SLC26A4 mutations exhibits diverse phenotypes, including congenital, acquired, progressive, and fluctuating impairments. This study investigates how pigmentation influences auditory dysfunction and immune responses in the stria vascularis using albino and pigmented Slc26a4 knockout (Slc26a4Δ/Δ) mice. We found that albino Slc26a4Δ/Δ mice exhibited significantly less severe hearing loss along with reduced macrophage activation than their pigmented counterpart did. Three-dimensional morphometric analyses revealed that macrophages in pigmented Slc26a4Δ/Δ mice were significantly larger, more rounded, and structurally distinct from those in albino mice, suggesting divergent activation states. PHATE-based trajectory analysis further confirmed that these macrophages follow separate activation pathways influenced by pigmentation. Transcriptomic profiling showed no upregulation of melanogenesis-related genes, implying that melanin accumulation arises from impaired degradation rather than increased synthesis. Functional enrichment analysis highlighted dysregulation in proteolysis and phosphate metabolism, implicating metabolic stress and chronic inflammation in disease progression. Based on these findings, we propose a multi-step pathophysiological cascade in which SLC26A4 deficiency leads to metabolic imbalance, pathological melanin accumulation, macrophage activation, and ultimately, progressive hearing loss. This work reveals a context-dependent dual role of melanin and demonstrates how genetic background and pigmentation influence immune responses and cochlear pathology. These insights may inform future strategies for individualized approaches to diagnosis and therapy in SLC26A4-related hearing loss.